Participation in four rounds of a French colorectal cancer screening programme with guaiac faecal occult blood test: a population-based open cohort study. (June 2015) - Denis, Bernard; Gendre, Isabelle; Perrin, Philippe
Objectives: Four randomized controlled trials have demonstrated the efficacy of screening using a guaiac faecal occult blood test (gFOBT) on colorectal cancer (CRC) mortality. Whether their results are transposable to the real world is unknown. This study aimed to assess the determinants of participation in the first four rounds of the CRC screening programme using a gFOBT implemented since 2003 in the Haut-Rhin (Alsace) part of the French national programme. Methods: We performed a population-based open cohort study of all residents aged 50–74, around 200, 000 people. They were invited by mail to participate every other year. The gFOBT kits (Hemoccult II) were first provided by general practitioners, and then directly mailed to persons who failed to comply. Results: The uptake decreased significantly across all rounds, from 54.3% to 47.1% (p < 0.0001), mainly in people younger than 60. The proportion of people screened by general practitioners increased significantly from 77.0% in the first round to 84.2% in the fourth (p < 0.01). Overall, 61.3% of the invited population participated at least once, and 14.3% had completed all the four tests. The colonoscopy uptake was around 91%, among the highest ever reported. Conclusions: Despite the involvement of general practitioners, the uptake and adherence to repeat testing are modest and deteriorate with time, so that the reduction in CRC mortality in reality will be significantly lower than that in the trials. The benefit-risk balance of the French programme is, at present, less favourable than that shown in the trials.